New Evaluation Model by Means of Mobile Technology. (2015) - Moldovan, Liviu
Abstract: This paper presents employment of mobile technology in order to turn the assessment process into a more simplified and learning friendly process. It is developed a new learning and evaluation model that comprises four evaluationlearning activities: pre-tests, learning, post-tests and comparison which allows instructor to organise teaching in many different ways. The four steps for the evaluation employment by means of the new Peer Learning Assessment Software ONE2ACT are described. Conclusions for the evaluation model and testing with the software demonstrate impressions of trainees and instructors regarding technological and methodological aspects of the evaluation. The success indicators in terms of effectiveness as well as quality and completion for software employment and assessment methodology are exemplified.